A obesidade e o advento da etnofarmacologia como base para o tratamento - FREITAS JUNIOR, Luciano Mamede de (2017)
Currently, obesity represents a global epidemic, with prevalence increasing especially in developing countries and the young population, requiring effective and safe treatment and control in order to improve quality of life, minimizing the occurrence of comorbidities and lethality. The National Health Surveillance Agency / Ministry of Health, through normative determinations, has drastically restricted the commercialization of synthetic drugs, with the consequence of the use of several conduits as alternatives for curing and / or reducing the diseases, with emphasis on the use of plants. Although the popular use of plant species for therapeutic purposes represents a millennial practice, the use of ethnobotanical and ethnopharmacological approaches, important tools in the selection of plants for research and development of new therapeutic options, is essential, thus avoiding or diminishing the probable risks and dangers of the use of plants for health. In this way, this proposal aimed to study the plants used as antiobesity and the advent of ethnopharmacology as a basis for treatment. The first part of the study consisted in the elaboration of a review article to compile the world-known species the treatment of obesity and, in parallel, a local survey was carried out in the fairs and markets of São Luis, Maranhão, Brazil, to evaluate the plants used for the treatment of obesity indicated by the marketers; the second stage resulted in the collection and identification of the plant species referenced in the ethnopharmacological survey as used in the treatment of obesity. The data obtained were presented in 2 scientific articles, as follows: the first article is a bibliographical survey of the plant species used in the treatment of obesity and had its results published in the American Journal of Translational Research; The second article dealing with the results of the ethnopharmacological survey conducted with the traders of medicinal plants submitted to the American Journal of Translational Research. With the results, it was possible to carry out a broad review of the studies reporting plants for the treatment of obesity, as well as to highlight the profile of the study population in the ethnopharmacological survey; to rescue popular knowledge about plant species used in obesity; investigate the form of use; identify the species concerned; record and document ethnobotanical, ethnopharmacological and toxicity aspects; to compare the popular information on the therapeutic properties attributed to the vegetal species inventoried to the scientific data and registered in the specialized literature.